Molecular Analysis of the Melanogenesis Inhibitory Effect of Saponins-Rich Fraction of Argania spinosa Leaves Extract - Myra O. Villareal; Thanyanan Chaochaiphat; Rachida Makbal; Chemseddoha Gadhi; Hiroko Isoda (Molecules, 2022)
Plant saponins are abundant and diverse natural products with a great potential for use in drug-discovery research. Here, we evaluated extracts of saponins-rich fractions of argan leaves and argan oil extraction byproducts (shell, pulp, press cake) for their effect on melanogenesis. Results show that from among the samples tested, only the saponins-rich fraction from leaves (ALS) inhibited melanin production in B16 murine melanoma (B16) cells. The mechanism of the melanogenesis inhibition was elucidated by determining the protein and mRNA expression of melanogenesis-associated enzymes tyrosinase (TYR), tyrosinase-related protein 1 (TRP1), and dopachrome tautomerase (DCT), and microphthalmia-associated transcription factor (MITF), and performing DNA microarray analysis. Results showed that 10 µg/mL ALS significantly inhibited melanogenesis in B16 cells and human epidermal melanocytes by 59% and 48%, respectively, without cytotoxicity. The effect of ALS on melanogenesis can be attributed to the decrease in TYR, TRP1, and MITF expression at the protein and mRNA levels. MITF inhibition naturally led to the downregulation of the expression of Tyr and Trp1 genes. Results of the DNA microarray analysis revealed the effect on melanogenesis-associated cAMP and Wnt signaling pathways’ genes. The results of this study suggest that ALS may be used in cosmeceuticals preparations for hyperpigmentation treatment.